Detox in a box marketing plan - Soares, Ana Teresa Santos (2020)
The purpose of this dissertation is to develop a marketing plan for Detox in a Box. It is a startup who sells smoothies, ready to settle, to companies. As a matter of fact, it operates in Porto and in the future in Lisbon, through different business models, such as: direct sale to companies and vending machines. The creation of the company was in March 2019 and currently needs help in better understanding the market, potential customers, profile target and some brand awareness measures. The methodology used to develop the plan was, on the one hand, secondary data through newspapers, national databases, and websites of different companies for market study. On the other hand, primary data through a questionnaire launched exclusively to the Portuguese working population, where it was possible to draw statistical conclusions and make two models of multiple regression, to perceive the willingness to use and pay the products of the Portuguese startup. Additionally, personal interviews with human resources managers, of some multinationals located in Lisbon, to understand in a more direct and objective way some potential marketing measures and the availability of having the products in their offices. Based on the analysis done throughout the thesis, some conclusions are: the need for more information on the benefits of this type of snacks during working hours; some measures to be adopted by the company to capture more effectively their customers, among others.